2019
DOI: 10.1111/jcmm.14325
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB p65 promotes ovarian cancer cell proliferation and migration via regulating mortalin

Abstract: Previous studies show that mortalin, a HSP70 family member, contributes to the development and progression of ovarian cancer. However, details of the transcriptional regulation of mortalin remain unknown. We aimed to determine whether NF‐κB p65 participates in the regulation of mortalin expression in ovarian cancer cells and to elucidate the underlying mechanism. Chromatin immunoprecipitation and luciferase reporter assay were used to identify mortalin gene sequences, to which NF‐κB p65 binds. Results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 51 publications
3
20
0
Order By: Relevance
“…Furthermore, we observed that miR-630 carried by EVs targeted the KLF6 expression in NFs, whereas over-expression of KLF6 could reverse the EVs-induced CAF activation and NF migration. Meanwhile, KLF6 can transactivate multiple genes that negatively regulate the NF-κB pathway, while activation of the NF-κB pathway was reported to accelerate the migration and invasion of OC cells ( Li et al, 2018 , 2019 ; Zheng et al, 2018 ). Accordingly, we documented that EVs activated the NF-κB pathway via the miR-630/KLF6 axis during CAF activation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed that miR-630 carried by EVs targeted the KLF6 expression in NFs, whereas over-expression of KLF6 could reverse the EVs-induced CAF activation and NF migration. Meanwhile, KLF6 can transactivate multiple genes that negatively regulate the NF-κB pathway, while activation of the NF-κB pathway was reported to accelerate the migration and invasion of OC cells ( Li et al, 2018 , 2019 ; Zheng et al, 2018 ). Accordingly, we documented that EVs activated the NF-κB pathway via the miR-630/KLF6 axis during CAF activation.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB p65 was reported to promote cell proliferation, invasion and migration in ovarian cancer [ 18 , 19 ]. To investigate whether NOX4 regulates expression of NF-κB p65, cells were transfected with either lentivirus carrying shNOX4 or control shNC, total proteins were extracted for Western blotting to analyze NF-κB p65 protein levels.…”
Section: Resultsmentioning
confidence: 99%
“…The NF-κB pathway, especially its important member P65, has a complicated relationship with cancer [ 25 , 26 , 27 , 28 ]. Shan et al demonstrated that P65 binds to the mortalin promoter and promotes ovarian cancer cell proliferation and migration via regulating mortalin [ 26 ]. Zhang et al showed that it can directly bind to the promoter of cyclin D1, mediating an increase in the protein’s expression [ 28 ].…”
Section: Discussionmentioning
confidence: 99%